The role of polymorphism of genes IL5 (–703) and IL5RA (–80) in formation of blood eosinophilia under pulmonary tuberculosis - K. O. Mikheyeva; V. V. Novitsky; O. I. Urazova; Yu. V. Kolobovnikova; M. D. Goncharov; I. O. Naslednikova (Бюллетень сибирской медицины)
With attracting contemporary molecular-genetic and immunological research methods, the article analyses etiopathogenetical factors of formation of eosinophilic blood reaction under pulmonary tuberculosis. It has been established that blood eosinophilia under pulmonary tuberculosis is reactive, mediated by hypersecretion, blood cells of IL-5-key eosinophil-activating mediator as well as excessive expression of IL-5R on the membrane of eosinophilic granulocytes. Besides, susceptibility to the emergence of eosinophilic blood reaction under tubercular infection is associated with the homozygous genotype CC and allele C of the polymorphic region C-703 T of the gene IL5 as well as with allele A and genotype AA of the polymorphic region G-80 A of the gene IL5RA.